2021
DOI: 10.3389/fped.2021.711979
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns and Outcomes of Growth Hormone Treatment Among Children in Israel Over the Past Decade (2004–2015)

Abstract: Objective: To assess a decade of growth hormone (GH) treatment patterns and outcomes in a real-world setting in Israel using a state-of-the-art computerized database.Methods: This large retrospective database study included 2,379 children initiating GH treatment in Maccabi Healthcare Services (between January 2004 and December 2014). Good adherence with therapy (proportion of days covered >80%) was assessed during follow-up.Results: At GH treatment initiation: 62.1% were boys; height standard deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
5
4
0
Order By: Relevance
“…If GH treatment had been continued for more than 3 years, the height SDS at the 3 rd year increased by 1.46 compared to baseline in both boys and girls (height SDS, boys: −2.48–−1.02, girls: −2.58–−1.12). These results were consistent with those of previous studies in which the height SDS increased by 0.40 to 0.57 from 6 months to the 1 st year after GH treatment and by 0.96–1.05 at the 3 rd year ( 4 , 5 , 30 32 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…If GH treatment had been continued for more than 3 years, the height SDS at the 3 rd year increased by 1.46 compared to baseline in both boys and girls (height SDS, boys: −2.48–−1.02, girls: −2.58–−1.12). These results were consistent with those of previous studies in which the height SDS increased by 0.40 to 0.57 from 6 months to the 1 st year after GH treatment and by 0.96–1.05 at the 3 rd year ( 4 , 5 , 30 32 ).…”
Section: Discussionsupporting
confidence: 93%
“…When considering both GH dose and the efficacy results comprehensively, GH treatment efficacy in this study was enough compared with that of previous studies, although the average GH dose in this study was lower than the recommended GH treatment dose. This revealed that the GH dose administered in a Korean clinical setting is lower than the recommended dose ( 29 , 30 , 33 , 34 ) and that effective treatment is possible even without prescribing a high dose of GH to children with ISS. Although the dose initially approved in Korea (0.067 mg/kg/day, 0.37 mg/kg/week, 0.40 mg/kg/week) is lower that the dose recommended in international guidelines (0.47 mg/kg/week), the phenomenon of administering less than the approved dose for patients with ISS was also seen in previous Korean studies by Nam HK et al in 2019 and Jeong HR et al in 2014, which showed significantly improved growth outcomes even with low doses ( 35 – 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…21,23,24 The main indications for treatment in our study were ISS and GH deficiency, similar to a previous cohort study from Israel, comprising 2379 children. 25 Univariate analysis of our rhGH treatment group demonstrated that male gender, older age at initiation of rhGH treatment and high SES were associated with increased risks for scoliosis. The higher SES may be explained by a bias resulting from differences in seeking medical evaluation and treatment behaviours according to SES.…”
Section: Discussionmentioning
confidence: 84%
“…Persistence studied using the Easypod autoinjector found median persistence with treatment to be 2.1 years ( 11 ). A retrospective database study of children initiating GH treatment in Israel found mean persistence of 3.6 ± 1.6 years, and 3.7% of children discontinued (gap of 365 years without treatment) ( 12 ). A recent US-based study found that 42.2% of pGHD children discontinued somatropin therapy (gap of >60 days without treatment) within 48 months of follow-up ( 13 ).…”
Section: Discussionmentioning
confidence: 99%